Spatial contrast sensitivity from star- to sunlight in healthy subjects and patients with glaucoma. (May 2019) - Bierings, R.A.J.M.; Overkempe, T.; van Berkel, C.M.; Kuiper, M.; Jansonius, N.M.
Abstract: Glaucoma is traditionally considered an asymptomatic disease until later stages. However, questionnaire studies revealed visual complaints related to various tasks, especially under extreme luminance conditions (such as outdoor at night on an unlit road or outside in the sun). We measured contrast sensitivity (CS) over a luminance range of 6 log units spanning the scotopic to photopic range and we aimed (1) to determine whether Weber's law also holds under extremely high luminance conditions and (2) to compare CS as a function of spatial frequency and luminance between glaucoma patients and healthy subjects. We included 22 glaucoma patients and 51 controls, all with normal visual acuity. For the second aim, we used a subgroup of 22 age-similar controls. Vertically oriented sine-wave gratings were generated with a projector-based setup (stimulus size 8x5 degrees). CS was measured monocularly at 1, 3, and 10 cycles per degree (cpd); mean luminance ranged from 0.0085 to 8500 cd/m 2 . ANOVA was used to analyze the effect of glaucoma, luminance, and spatial frequency on logCS. In controls, Weber's law held for 3 and 10 cpd; for 1 cpd, CS dropped above 1000 cd/m 2 (P = 0.003). The logCS versus log luminance curves did not differ grossly between patients and controls (P = 0.14; typically 0–0.2 log units); the difference became larger with decreasing luminance (P = 0.003) but did not depend clearly on spatial frequency (P = 0.27). We conclude that differences between glaucoma and healthy were relatively modest for the spatially redundant, static stimulus as used in the current study.